Phytochemicals targeting glycolysis in colorectal cancer therapy: effects and mechanisms of action - Zhan, Lu; Su, Fangting; Li, Qiang; Wen, Yueqiang; Wei, Feng; He, Zhelin; Chen, Xiaoyan; Yin, Xiang; Wang, Jian; Cai, Yilin; Gong, Yuxia; Chen, Yu; et al. (Frontiers in Pharmacology, 2023)
Colorectal cancer (CRC) is the third most common malignant tumor in the world, and it is prone to recurrence and metastasis during treatment. Aerobic glycolysis is one of the main characteristics of tumor cell metabolism in CRC. Tumor cells rely on glycolysis to rapidly consume glucose and to obtain more lactate and intermediate macromolecular products so as to maintain growth and proliferation. The regulation of the CRC glycolysis pathway is closely associated with several signal transduction pathways and transcription factors including phosphatidylinositol 3-kinases/protein kinase B/mammalian target of rapamycin (PI3K/AKT/mTOR), adenosine 5'-monophosphate (AMP)-activated protein kinase (AMPK), hypoxia-inducible factor-1 (HIF-1), myc, and p53. Targeting the glycolytic pathway has become one of the key research aspects in CRC therapy. Many phytochemicals were shown to exert anti-CRC activity by targeting the glycolytic pathway. Here, we review the effects and mechanisms of phytochemicals on CRC glycolytic pathways, providing a new method of drug development.